Degradabilidade do capim-elefante (Pennisetum purpureum, Schum.) e da cana-de-açúcar (Saccharum officinarum, L.) mais uréia no rúmen de vacas mestiças Holandês × Zebu em lactação Rumen degradability of elephantgrass (Pennisetum purpureum, Schum.) and sugarcane (Saccharum officinarum, L.) plus urea in crossbred lactating cows - F.C.F. Lopes; L.J.M. Aroeira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 1999)
Elephantgrass shows a high stocking rate only during the rainy season. Forage production is drastically reduced in the dry season. One of the alternatives to minimize this problem is the supplementation with sugarcane plus urea. In this trial the main goal was to estimate the dry matter intake (DMI) of elephantgrass, chopped sugarcane plus 1% urea and their degradability in three lactating (11.6kg/milk/day) rumen fistulated crossbred cows (472kg/L.W.) grazing elephantgrass during the dry season. The cows had access during three consecutive night to the paddocks grazed every 30 days in a stocking rate, of 4.5 cows/hectare. Between the two milking times, cows received chopped sugarcane plus 1% urea. The DMI was on average 1.01%/L.W. for the elephantgrass and 0.88%/L.W. for the sugarcane plus 1% urea. Total DMI, taking into account both roughage and concentrate (2kg/cow/day) was 2.25%/L.W. The effective rumen degradability (ED), considering the rate of passage in the rumen of 5%/hour was 44.46% for elephantgrass and 41.94% for sugarcane plus 1% urea, DM. The elephantgrass ED crude protein was 48.58% and its neutral detergent fiber 33.82%. During the dry season lactating crossbred cows grazing elephantgrass have to receive a roughage supplement and concentrate to produce around to 12kg of milk per day.